If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(-4 + 3x) = 0 (-4 * x + 3x * x) = 0 (-4x + 3x2) = 0 Solving -4x + 3x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), 'x'. x(-4 + 3x) = 0Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-4 + 3x)' equal to zero and attempt to solve: Simplifying -4 + 3x = 0 Solving -4 + 3x = 0 Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 3x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + 3x = 0 + 4 3x = 0 + 4 Combine like terms: 0 + 4 = 4 3x = 4 Divide each side by '3'. x = 1.333333333 Simplifying x = 1.333333333Solution
x = {0, 1.333333333}
| 9/7*67/42 | | 9y^3-11y^2+6y=11y^2-6y+17 | | -6(-2x+3)= | | pi*2=3.18 | | x^3+5x^2-12x+6=(x-1)(ax^2+bx+c) | | -3x^2-21x+24= | | 5-4=30 | | 6x^3+5x^2-12x+6=(x-1)(ax^2+bx+c) | | 8(5x-4)= | | 0.09xX=95.41 | | 2/3=3x/20 | | 3x-15=(2x+10) | | 6x+10=6x | | 2.7x+13.758=4-2.97x | | 4-2m+4m+1= | | 8+5y=24 | | 4*x=2.5 | | (-x+9)*4= | | 7a-20=80 | | 3(2y+5)=30 | | 23x-5=25x-5 | | 2x+5=133 | | Y=58x+228 | | 7=5k-3 | | 5x-1=-5x+1 | | 7/2*63=7/2*2/7 | | M-5=11 | | (-x+7)*3= | | (g-7)(g+9)= | | 4v=8e-g | | 10m+3=38 | | 0.9=-log |